Economic Analysis of Pursat Orange Production in Cambodia: A Qualitative Case Study - POK, Phearak; CHHAY, Kongkea; ROS, Rvauth; DY, Putheara (MASI Mandiri Edukasi, 2024)
Economics is crucial in all countries, with no exception in Cambodia. There are different factors contributing to economic development. The current study thoroughly analyses the economic factors of Pursat orange production in Cambodia, including production expenses, income generation, profits, and the broader economic impacts on households and the national economy. By gathering a wide range of information from Pursat orange growers, the study uses various economic principles and approaches to assess the economic viability and possibility of Pursat orange cultivation as a long-term revenue stream. The current study employed a qualitative design to identify and analyse the primary components of production costs, evaluate the impact of revenue generation mechanisms, and determine the key determinants of profitability and economic sustainability in Pursat orange farming, elucidating their contributions to the overall financial landscape and informing decision-making processes among stakeholder. The results emphasise Pursat oranges' importance for increasing household income and promoting economic development in Cambodia. Additionally, the research provides opportunities for future investigations, indicating possible areas for further exploration, like the influence of technological progress on production effectiveness, the significance of market trends in determining profit, and the potential socio-economic advantages of value-added activities in the Pursat orange supply chain. The research provides valuable insights for policymakers, stakeholders, and farmers by illuminating the economic aspects of Pursat orange production. It emphasises opportunities to improve the sector's resilience and its beneficial effects on livelihoods and overall economic growth.